Privacy in Islam as a Guide to Housing Development - Zahari Mahad Musa; Mohd Farid Ravi Abdullah; Abur Hamdi Usman; Azwar Iskandar (UIN Sunan Gunung Djati Bandung, 2021)
The dwelling house is part of the basic needs of human life. In Islam, the designation of a place as a dwelling house has its importance. The dwelling house is not only seen as a sanctuary for oneself and one’s property, but it is also significant in providing space for privacy. This paper discusses privacy related to a dwelling house in Islamic jurisprudence. The discussion will focus on the importance of the privacy rules for a dwelling house to guide the parties involved in housing development. The type of research is qualitative with a socio-historical approach. The results indicate that Islam provides a balance between social life and the need to be alone. The principles of privacy for a dwelling house not only show the security of shariah objectives, but they also guide the construction industry with divine guidance in sustainable human development.